Effect of bioagents on Alternaria leaf spot and withaferin content of Withania somnifera (L.) Dunal. - ANUBHA UPADHAYAY, VIBHA* and (Indian Phytopathology, 2016)
Leaf blight of Ashwagandha (Withania somnifera) is the most prevalent disease in almost all the cultivated areas of the crop. Four strains of Trichoderma asperellum and two strains of Trichoderma harzianum were tested against the test pathogen. Similarly, eight strains of Pseudomonas fluorescens were also evaluated against the test pathogen through dual culture technique. Besides, neem based formulations were tested to find out the most suppressive against the pathogen through poison food technique. The compatibility of organic amendment with bioagents was also tested under in vitro conditions. The best Trichoderma isolate, Pseudomonas fluorescens and FYM were evaluated individually and in-combination, with or without spray of Neem based formulation, for the management of Alternaria leaf blight under field conditions. The field experiment was conducted in split plot design with main plot comprises of spray of Azadirachtin (0.15%) and NSKE (neem seed kernel extract) and sub-plot of biological combinations incorporated into the soil. The withaferin A content was estimated through standard method. Among the different isolates of Trichoderma spp., the highest mycelial growth inhibition was observed with T. asperellum 13 against Alternaria alternata. However, Pseudomonas fluorescens isolate 21 was found highly suppressive towards the pathogen. Among neem formulations mycelial growth inhibitory effect of Azadirachtin (0.30 percent) was the highest but statistically at par with Azadirachtin (0.15 percent). The compatibility studies revealed that the FYM was compatible with both T. asperellum 13 and P. fluorescens 21. It was found that the Azadirachtin (0.15%) x T. asperellum @ 106 cfu/ml + P. fluorescens 21. @ 109 cfu/ml was the best treatment for reducing the Alternaria leaf blight and enhancing the root and seed yield.